Propeller-Shaped Self-Assembled Molecular Capsules: Synthesis and Guest Entrapment - Satha, Pardhasaradhi; Illa, Giriteja; Purohit, Chandra Shekhar (Crystal growth & design, 2013)
Molecular containers or supramolecular capsules are a subject of great interest because of their potential utilizations in various fields of chemistry, medicine, and nanoscience. They have been utilized as nanovessels for reactions and targeted drug delivery in recent years. Cyclotricatechylene (CTC) is a bowl-shaped molecule in its crown structure. It has six phenolic groups as potential hydrogen bond donors. In this work, we utilize this hydrogen bonding capability of CTC to generate supramolecular complexes with hydrogen bond acceptors such as 4,4′-bipyridine, pyrazine, 2,2′-bipyridine, and phenanthroline. These supramolecular entities were studied in the solid state by X-ray crystallography and scanning electron microscopy. They are not soluble in low polar solvents. Therefore, the hydrogen bonding behavior in solution could not be studied by NMR. Except in the case of pyrazine, capsular supramolecular assemblies were formed in all the cases. One of these capsules was studied for guest entrapment. Planar molecules such as naphthalene and pyrene were trapped inside its cavity with a little reorganization of the capsular assembly.